2017
DOI: 10.1016/j.foodpol.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing food insecurity in Latin America and the Caribbean using FAO’s Food Insecurity Experience Scale

Abstract: The complexity of the operational concept and definition of food insecurity has complicated the study of the 'food insecure' and efforts to determine clear policy directions. Previous findings on the prevalence and severity of food insecurity are inconsistent and often depend on the measure used. To overcome limitations in food security measurement, the Food and Agriculture Organization of the United Nations developed the Food Insecurity Experience Scale, which is the first survey protocol to measure people's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
68
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 38 publications
11
68
1
2
Order By: Relevance
“…This is consistent with other studies in Latin America, in which overcrowding and low socioeconomic status have been cited as factors contributing to household food insecurity [14,40,41]. Beyond the total number of people in the household, household life cycle factors including household composition, age of household members, and marital status also influence individual and household food security [41][42][43]. Additionally, as gender influences food production, distribution, and consumption, it also has direct implications for individual and household food security [4].…”
Section: Factors Associated With Seasonal Food Insecuritysupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with other studies in Latin America, in which overcrowding and low socioeconomic status have been cited as factors contributing to household food insecurity [14,40,41]. Beyond the total number of people in the household, household life cycle factors including household composition, age of household members, and marital status also influence individual and household food security [41][42][43]. Additionally, as gender influences food production, distribution, and consumption, it also has direct implications for individual and household food security [4].…”
Section: Factors Associated With Seasonal Food Insecuritysupporting
confidence: 92%
“…In this study, individuals from larger and poorer households reliant on subsistence agriculture were more likely than individuals from smaller and wealthier households to have insufficient food availability and access. This is consistent with other studies in Latin America, in which overcrowding and low socioeconomic status have been cited as factors contributing to household food insecurity [14,40,41]. Beyond the total number of people in the household, household life cycle factors including household composition, age of household members, and marital status also influence individual and household food security [41][42][43].…”
Section: Factors Associated With Seasonal Food Insecuritysupporting
confidence: 91%
See 1 more Smart Citation
“…While it is not particularly surprising that having more education is associated with less food insecurity, the nding that older persons are less likely to experience food insecurity may run counter to that of other nations. For example, in Latin America and in the US, older individuals are often at higher risk [16,22]. However, based on the knowledge of our Bahamian co-author, Bahamians have long held traditions to rst feed the elders in the home, which may explain the effect.…”
Section: Discussionmentioning
confidence: 99%
“…Source: FAO 2014. http://www.fao.org/in-action/voices-of-the-hungry/background/en/ researchers measured criteria validity of the tool, results showed that despite the diversity in the global population, food insecurity was associated with commonly cited determinants and consequences of food security such as national income, health, and well-being (Jones 2017;Smith et al 2017b).…”
Section: Contribution To Knowledge Benefit (Theory Development)mentioning
confidence: 99%